The Association between the Urinary Excretion of Trimethylselenonium and Trimethylsulfonium in Humans - Lajin, Bassam (PLoS One, 2016)
Hydrogen sulfide is a signaling molecule that plays important roles in several physiological processes, and its methylation product trimethylsulfonium (TMS) is a natural constituent of human urine that could serve as a biomarker for hydrogen sulfide. In vitro studies showed that the enzyme indole-ethylamine N-methyltransferase (INMT) is responsible for the production of trimethylsulfonium as well as its selenium analogue trimethylselenonium (TMSe). Marked inter-individual variability in TMSe production is associated with genetic polymorphisms in the INMT gene, but it remains unclear whether these polymorphisms affect substrate specificity or general enzymatic activity. Therefore, we explore the association between the TMS and TMSe production phenotypes. Caucasian volunteers were recruited and grouped according to their TMSe status into “TMSe producers” and “TMSe non-producers”, and morning urine samples were collected over 5 consecutive days from each volunteer. A total of 125 urine samples collected from 25 volunteers (13 TMSe producers and 12 TMSe non-producers) were analyzed for total selenium and total sulfur using inductively coupled plasma mass spectrometry (ICPMS), trimethylselenonium using HPLC/ICPMS, and trimethylsulfonium using HPLC/electrospray ionization—triple quadrupole—mass spectrometry (ESI-QQQ-MS). Although there was no correlation between TMS and TMSe urinary levels within the “TMSe producers” group, the “TMSe producers” had urinary levels of TMS 10-fold higher than those of the “TMSe non-producers” (P < 0.001). This result indicates that stratification according to TMSe status or genotype is crucial for the correct interpretation of urinary TMS as a possible biomarker for hydrogen sulfide body pools.